Engineering properties of weathered sedimentary rock masses for surface excavation works [electronic resource] - Edy Tonnizam Mohamad 485143; Khairul Anuar Kassim 562339 (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Doktor Falsafah (Fakulti Kejuteraan Elektrik)) - Universiti Teknologi Malaysia, 2007